Influence of exercise order on upper body maximum and submaximal strength gains in trained men - Assumpção, Claudio Oliveira (2013)
The purpose of this study was to investigate the influence of exercise order on one-repetition maximum (1-RM) and ten-repetition maximum (10-RM) strength gains after 6 weeks of resistance training (RT) in trained men. Sixteen men were randomly assigned into two groups based on the order of exercises performed during training sessions: a group that performed large muscle group exercises first and progressed to small muscle group exercises (LG-SM); while a second group performed the opposite sequence and started with small muscle group exercises and progressed to large muscle group exercises (SM-LG). Four sessions of RT were conducted per week; all exercises were performed for three sets of 8–12 repetitions with 1-min rest intervals between sets. Maximal and submaximal strength were assessed at baseline and after 6 weeks of RT with 1-RM and 10-RM testing for the bench press (BP), lat pulldown (LPD), triceps pulley extension (TE) and biceps curl (BC), respectively. Two-way ANOVA for the 1-RM and 10- RM tests indicated a significant group x time interaction. The 1-RM values significantly increased for all exercises in both groups (P<0.05), but were not significantly different between groups. However, effect size (ES) data indicated that the LG-SM group exhibited a greater magnitude of gains (1-RM and 10-RM) for the BP and LPD exercises. Conversely, ES indicated that the SM-LG group exhibited a greater magnitude of gains (1-RM and 10-RM) for the TE and BC exercises. In conclusion, the results suggest that upper body movements should be prioritized and performed according to individual needs to maximize maximal and submaximal strength.